Relationship Marketing:The lesson That today's Marketer Ought to Learn (a Marketer' - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Much of the work in marketing literature has endeavored greatly to explore the prevailing transition of the marketing paradigm in order to propose the nature and destiny that marketing as a living process should reflect and, entail. As such there is not much debate that can allude inadequacy of the description of how relationship marketing should be like and be conducted, and so it is the same for the conditions in which it could help a marketer realize or fail to realize its benefits. This paper undertakes a different approach in examining some of the critical issues surrounding the paradigm. It will entail the examination of relationship marketing by trying to critically answer the following questions: What is its current and future visions? How could we attempt a detailed definition of relationship marketing? What relationship marketing is and is not? Who will build and manage relationship marketing? What factors are necessary for successful relationship marketing? Does relationship marketing really work? and the Epilogue.